Egg injection of ascorbic acid stimulates leucocytosis and cell proliferation in the bursa of Fabricius - Sgavioli, Sarah [UNESP]; Borges, Liliana Longo [UNESP]; de Almeida, Vitor Rosa [UNESP]; Thimotheo, Mariana [UNESP]; de Oliveira, João Ademir [UNESP]; Boleli, Isabel Cristina [UNESP] (My University, 2013)
Broiler chicks with high immune defense potential at hatching are of great value to the poultry industry. Heat stress can have immunosuppressive or immune stimulatory effect and Ascorbic Acid (AA) acts as anti-stressor and has important physiological functions in bird immune system development. This study aimed to assess the effect of intra egg injection of AA before incubation on development of the bursa of Fabricius and leukocyte parameters in chicks from eggs incubated at thermoneutral and hot temperatures. Fertile eggs from broiler breeder chickens were used in a 5 × 2 factorial design with 5 treatments (noninjected and thus non-perforated and injected with 0, 2, 4 and 6% AA in 100 pL of water) and 2 incubation temperatures (thermoneutral: 37.5°C and hot: 39.0°C). The total leukocyte count; percentages of thrombocytes, basophils, eosinophils, monocytes and heterophils; weight; and bursal index remained unaffected by incubation temperature and AA dose. Bursal follicle area decreased in chicks from non-injected eggs when incubated at hot temperatures. With intra egg injection of 4 and 6% AA, bursal follicle size increased in eggs incubated at thermoneutral temperature and decreased at hot temperature compared to no AA injection. Cell proliferation in follicles increased by injecting 2% AA, whereas the percentage of lymphocytes increased by injecting 4 and 6% AA. The data show that AA acts as a dose- and temperature- dependent immunomodulator and that 4 and 6% AA doses stimulate egg bursal development and lymphocytosis. These findings suggest that intra egg injection of AA produces chicks with higher potential for immune defense against challenges in the field. © Asian Network for Scientific Information, 2013.
Keywords: Chicks; Cloacal sac; Leucocytes; Mitosis; Vitamin C